Insecticidal effects of nano-encapsulated lemongrass essential oil on the population parameters of Spodoptera frugiperda using two-sex life table - Samar Sayed Ibrahim; Magdy Youssef El-Kholy; Shehata El-Sayed Mohamed Shalaby (Scientific Reports)
Abstract Essential oils derived from plants have demonstrated their efficacy in controlling insects; however, their poor physical characteristics restrict their widespread application. In this study, nano-encapsulation employing emulsification followed by ultrasonication technique has improved the insecticidal efficacy of lemongrass oil (LGO) against Spodoptera frugiperda. Beta-cyclodextrin (β-CD) and gum Arabic (GA) were used as coating materials to protect the vital components of LGO. Different concentrations of LGO pure and nano-capsule formulations have been used to examine the biological development of S. frugiperda 1st larval instar using two sex life table. D-Limonene, E-Citral, and Z-Citral were identified as the main compounds in LGO by GC–MS analysis. The oil concentration affected the physical properties of nano-capsules. The LGO nano-capsules had particle sizes ranging from 279.63 to 471.93 nm and an encapsulation efficiency between 51.94 and 83.59%. Following 96 h, the LGO:β-CD/GA treatment of S. frugiperda had a lower LC50 value (1.52%) than the LGO treatment (2.48%), indicating that the nano-capsules were more toxic. Nano-capsules had a significant adverse effect on the life table parameters of S. frugiperda. The results of this study indicate that encapsulating LGO with β-CD/GA inclusion enhanced the efficacy of lemongrass oil against S. frugiperda.